Nutrient effects of modification of shifting cultivation in west Africa - Juo, A.S.; Kang, B.T. (1989)
Recycling of plant residues, fertilizer use and inclusion of trees and perennials in crop fields are key components in systems for improved food crop production on infertile soils in the forest regions of West Africa. 2 On Alfisols of pH 5.5 or higher in the forest and forest-savanna transitional zones, systems including food crop-cover crop rotation, minimum tillage and the judicial use of fertilizer can sustain yields on small farms for 10 years or more without reverting land to bush fallow. Inter-planting leguminous trees such as Leucaena leucocephala with annual food crops is shown to improve food crop yields. The leguminous trees fix atmospheric nitrogen, recycle mineral nutrients from the subsoil, and prevent soil erosion and run-off water on sloping land. 3 On strongly leached acid soils (i.e. Ultisols and Oxisols) in high-rainfall regions, nutrient cycling and green manuring are less effective because of subsoil infertility. Intensive food crop production on such soils requires costly inputs of fertilizer and lime. However, experiments have shown that periodic application of small dosages of lime can sustain a moderate crop yield. Gradual saturation of subsoil horizons with calcium is a prerequisite for effective recycling of nutrients in agricultural systems in the high-rainfall region.